ENVIRONMENTAL MANAGEMENT BEHAVIOR: The Relation Between Environmental Ethic Cognition, Perception on Environmental, and Responsibility in Environmental Conservation With Environmental Management Behavior, The Student of STIE Mulia Pratama in Bekasi, 2011 - Darlius Darlius (Mulia Pratama, 2015)
The objective of research is to study the relationship between environmental ethic cognition, the perception on environmental, and the responsibility in environmental conservation with environmental management behavior. The research is carried out campus environmental of STIE Mulia Pratama with 228 respondents (n = 228). Who are taken by random and simple sampling. The respondents are University Students, the data are analyzed by simple regression, multiple regression, simple correlation and multiple correlation. The study shows that there are positive correlation between, 1) Environmental ethic cognition with environmental management behavior, 2) Environmental perception with environmental management behavior, 3) The responsibility of environmental conservation with environmental management behavior, and 4) Moreover there is positive relationship between environmental ethic cognitionr, environmental perception, the responsibility of environmental conservation with environmental management behavior